Potential errors in conventional DOT measurement techniques in shake flasks and verification using a rotating flexitube optical sensor - Hansen, Sven (BioMed Central, 2011)
BACKGROUND: Dissolved oxygen tension (DOT) is an important parameter for evaluating a bioprocess. Conventional means to measure DOT in shake flasks using fixed Clark-type electrodes immersed in the bulk liquid are problematic, because they inherently alter the hydrodynamics of the systems. Other approaches to measure DOT that apply fluorescing sensor spots fixed at the inside wall of a shake flask are also suboptimal. At low filling volumes for cultivating microorganisms with a high oxygen demand, the measured DOT signal may be erroneous. Here, the sensor spot is sometimes exposed to gas in the head space of the flask. Merely repositioning the sensor spot elsewhere in the flask does not address this problem, since there is no location in the shake flask that is always covered by the rotating bulk liquid. Thus, the aim of this prospective study is first, to verify the systemic error of Clark-type electrodes for measuring DOT in shake flasks. The second principle aim is to use the newly built "flexitube optical sensor" to verify potential errors in conventional optical DOT measurements based on fixed sensor spots. RESULTS: With the Clark-type electrode, the maximum oxygen transfer capacity in shake flasks rose compared to that of an analogous system without an electrode. This proves changed hydrodynamics in the system with the Clark-type electrode. Furthermore, regarding the sensor spot experiments under oxygen-limited conditions where the DOT value ought to approach zero, the acquired signals were clearly above zero. This implies that the sensor spot is influenced by oxygen present in the headspace and not only by oxygen in the bulk liquid. CONCLUSIONS: The Clark-type electrode is unsuitable for measuring DOT. Moreover, the newly built rotating flexitube optical sensor is useful to verify potential errors of conventional optical DOT measurement techniques applying fixed sensor spots.